2020
DOI: 10.1515/jmbm-2020-0005
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and properties of tin slag polyester polymer concrete confined with FRP composites under compression

Abstract: Polymer concrete (PC) has acquired niche in construction industry due to superior mechanical properties, recyclability and adoption of variety of aggregates. This workpresents compressive behavior and properties of one such novel PC i.e. tin slag/polyester polymer concrete. Comparable siliceous content of tin slag was considered promising to provide better mechanical strength as in natural aggregates. Cylindrical short column specimens were fabricated to be tested under quasi-isostatic loading rate of 1 mm/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Based on the study from Faidzal et al (2018), two main conclusions are accepted, which are finer size tin slag aggregate and 70:30 aggregate-resin mixture ratio will result in highest strength TSPC. Then, Shakil and Hassan (2020) have performed a further study in TSPC by introducing two main approaches but still based on Faidzal study as reference. First is to formulate gap graded using tin slag aggregates with mixture of coarse and fine size particles.…”
Section: Highlight On Previous Study In Tin Slag As Aggregates In Polymer Concretementioning
confidence: 99%
See 2 more Smart Citations
“…Based on the study from Faidzal et al (2018), two main conclusions are accepted, which are finer size tin slag aggregate and 70:30 aggregate-resin mixture ratio will result in highest strength TSPC. Then, Shakil and Hassan (2020) have performed a further study in TSPC by introducing two main approaches but still based on Faidzal study as reference. First is to formulate gap graded using tin slag aggregates with mixture of coarse and fine size particles.…”
Section: Highlight On Previous Study In Tin Slag As Aggregates In Polymer Concretementioning
confidence: 99%
“…In Shakil and Hassan (2020) study, the researcher has performed an experiment to analyze the compression behavior of TSPC under one and two-layer glass fiber reinforced polymer (GFRP) and carbon fiber-reinforced polymer (GFRP) confinement. Upon compressive test on unconfined TSPC specimen, the highest strength is specimen with 4 mm + 2 mm tin slag particle size with 37.71 MPa.…”
Section: Highlight On Previous Study In Tin Slag As Aggregates In Polymer Concretementioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have been conducted on the use of TS as a fine aggregate replacement. Shakil and Hassan [12] evaluated the properties of TS polyester polymer concrete. The compressive strength test showed that samples attained a strength of 125.07 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…While in another quarter, polymer chemical admixtures was utilised effectively to modify the cement composites with enhanced properties observed after some tests were performed [7]. Cement mortars modified with polymers tend to have improved adhesion between fibers and matrix coupled with reduced per- meability because of low porosity [8,9]. Such modified systems possess improved flexibility and crack-bridging potential because of their low elastic modulus [10].…”
Section: Introductionmentioning
confidence: 99%